Implementation
Haskell

Be concise.

Be useful.

All contributions dictatorially edited by webmasters to match personal tastes.

Please do not paste any copyright violating resource.

Please try to avoid dependencies to third-party libraries and frameworks.

Other implementations
import java.util.List;
static <T> void reverse(List<T> x){
	int n = x.size();
	for(int i=0;i<n/2;i++){
		T tmp = x.get(i);
		x.set(i, x.get(n-i-1));
		x.set(n-i-1, tmp);
	}
}
x.reverse!
x = reversed(x)
import std.algorithm;
reverse(x);
for i, j := 0, len(x)-1; i < j; i, j = i+1, j-1 {
	x[i], x[j] = x[j], x[i]
}
import java.util.Collections;
Collections.reverse(x);
$x = array_reverse($x, true);
my @list = ('words', 'of', 'list', 'a', 'reverse');
my @reversed = reverse @list;
x = x.reverse();
let y: Vec<_> = x.iter().rev().collect();
import std.range;
auto y = x.retro;
x.reversed.toList()
var n,i: integer;
[...]
n:= length(x);
setlength(x, n+1);
for i := 0 to (n div 2)-1 do
	begin
		x[n] := x[i];
		x[i] := x[n-i-1];
		x[n-i-1] := x[n];
	end;
setlength(x, n);
var n,i: integer;
	tmp:TElement;
[...]
n:= length(x);
for i := 0 to (n div 2)-1 do
	begin
		tmp := x[i];
		x[i] := x[n-i-1];
		x[n-i-1] := tmp;
	end;
lists:reverse(List)
(reverse x)
Enum.reverse(x)
rev = {}
for i=#x, 1, -1 do
	rev[#rev+1] = x[i]
end

-- in-situ reversal
function reverse(t)
  local n = #t
  local i = 1
  while i < n do
    t[i],t[n] = t[n],t[i]
    i = i + 1
    n = n - 1
  end
end
System.Collections.Generic;
x.Reverse();
#include <algorithm>
std::reverse(begin(x), end(x));
val items = List(1, 2, 3, 4, 5)
items.reverse
with Ada.Containers.Vectors;
use Ada.Containers;
X.Reverse_Elements;
x = x[::-1]
int *p1 = x;
int *p2 = x + N-1;

while (p1 < p2)
{
    int temp = *p1;
    *(p1++) = *p2;
    *(p2--) = temp;
}
(reverse x)
list = [1, 2, 3, 4, 5]
Enum.reverse(list)
(reverse x)
let mut x = vec![1,2,3];
x.reverse();